2023
DOI: 10.3390/tropicalmed8070377
|View full text |Cite
|
Sign up to set email alerts
|

One Health Approach in Serosurvey of Toxoplasma gondii in Former Black Slave (Quilombola) Communities in Southern Brazil and Among Their Dogs

Giovanni Kalempa Panazzolo,
Louise Bach Kmetiuk,
Orlei José Domingues
et al.

Abstract: Brazilian quilombos are rural semi-isolated remnant communities of former black slaves and their descendants who traditionally maintained themselves through archaic subsistence livestock and agriculture practices and historically lacked specific public health policies. Although such individuals and their dogs may be exposed to zoonotic pathogens such as Toxoplasma gondii, no study to date has assessed these human-animal populations together. Populations in four different Brazilian quilombos in southern Brazil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…In Brazil, serosurveys and a review study [ 62 ] have indicated no association between consumption of raw meat and toxocariasis [ 13 , 53 , 63 ]. As previously shown for quilombola communities, although having low consumption of raw and undercooked meat, the logistic regression showed that those individuals who said they consumed raw or undercooked game meat were 2.4-fold more likely ( P = 0.042, 95% CI = 1.1–5.9) to be seropositive for Toxoplasma gondii [ 64 ].…”
Section: Discussionsupporting
confidence: 60%
“…In Brazil, serosurveys and a review study [ 62 ] have indicated no association between consumption of raw meat and toxocariasis [ 13 , 53 , 63 ]. As previously shown for quilombola communities, although having low consumption of raw and undercooked meat, the logistic regression showed that those individuals who said they consumed raw or undercooked game meat were 2.4-fold more likely ( P = 0.042, 95% CI = 1.1–5.9) to be seropositive for Toxoplasma gondii [ 64 ].…”
Section: Discussionsupporting
confidence: 60%
“…Furthermore, despite the absence of seropositivity in individuals with AHD and the comparatively low seroprevalence in dogs in the present study, B. PLOS NEGLECTED TROPICAL DISEASES canis outbreaks should be considered in such human populations due to the high burden and recurrent character of B. canis circulation in high-density dog populations and the constant introduction of susceptible animals. These findings in dogs highlight human vulnerability as a risk factor for brucellosis, as has been observed for other zoonotic diseases in homeless, indigenous, and quilombola communities [45][46][47][48]. In addition, negative results for individuals with AHD may indicate that B. canis has the lowest zoonotic potential in the genus Brucella [12,17].…”
Section: Discussionmentioning
confidence: 69%
“…A total of 83/153 (54.2%) cases were reported in slaughterhouse workers in Medellín, Colombia [ 27 ], 13/54 (24.1%) in veterinary professionals and students in Quito, Ecuador [ 28 ], and 1/99 (1.0%) in the healthy population of Buenos Aires, Argentina [ 29 ]. The study of vulnerable populations has brought a different perspective on how zoonotic diseases affect populations, alerting them to new associated risk factors and demanding a One Health approach to human, animal, and environmental health [ 30 ]. In the Brazilian Amazon, an indigenous population was investigated, which resulted in no (0/73) seropositive individuals [ 31 ].…”
Section: Discussionmentioning
confidence: 99%